Initiating Electron Transfer in Doubly Curved Nanographene Upon Supramolecular Complexation of C-60 - Zank, Simon; Fernandez-Garcia, Jesus M.; Stasyuk, Anton J.; Voityuk, Alexander A.; Krug, Marcel; Sola, Miquel; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2021)
The formation of supramolecular complexes between C-60 and a molecular nanographene endowed with both positive and negative curvatures is described. The presence of a corannulene moiety and the saddle shape of the molecular nanographene allows the formation of complexes with 1:1, 1:2, and 2:1 stoichiometries. The association constants for the three possible supramolecular complexes were determined by H-1 NMR titration. Furthermore, the stability of the three complexes was calculated by theoretical methods that also predict the photoinduced electron transfer from the curved nanographene to the electron acceptor C-60. Time-resolved transient absorption measurements on the ns-time scale showed that the addition of C-60 to NG-1 solutions and photo-exciting them at 460 nm leads to the solvent-dependent formation of new species, in particular the formation of the one-electron reduced form of C-60 in benzonitrile was observed.
CRIS-Team WoS Importer:2022-01-07